UJI KINERJA ALAT PANEN JAGUNG COMBINE HARVESTER MAXXI CORN TIPE-G DI DESA LOPANA KECAMATAN AMURANG TIMUR KABUPATEN MINAHASA SELATAN - Rodrigo J. Mokalu; Lady C. Ch. E. Lengkey; Frans Wenur (COCOS, 2022)
AbstractThe purpose of this study was to describe the Describing the condition and performance of thetool during harvesting using Combine Harvester and calculate capacity and field efficiency usingCombine Harvester. The results showed that the average condition and performance of the toolwith an average operating speed of 0.38 m/sec. The capacity of the results of the mapis 107.6 kgand for the total yield of 732.9 kg / ha. On average in this study the theoretical field capacity was0.277 ha/h, the effective field capacity was 0.147 ha/h and the field efficiency was 52.7%.Key words: corn, combine harvester, field capacity, the field efficiency